2020
DOI: 10.1177/1742395319899466
|View full text |Cite
|
Sign up to set email alerts
|

Competencies and training of health professionals engaged in health coaching: A systematic review

Abstract: Objective A systematic review was undertaken in order to evaluate the competencies of primary healthcare professionals who are engaged with health coaching patients with chronic health conditions. Methods The databases CINHAL, EMBASE, PubMed, PsychINFO and SCOPUS were searched to identify peer reviewed papers referring to competencies of health professionals engaged in health coaching. Results Nine key competencies that health professionals met and which resulted in successful patient outcomes from health coac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
(115 reference statements)
0
15
0
Order By: Relevance
“…In order to determine if pharmacists from international jurisdictions meet the competencies required to health coach a comparative document analysis was used (Sandelowski, 2000). The enabling competencies for health coaches (Singh et al, 2020) were used as predefined categories for analysis, and the enabling competencies/key competencies/ competencies/ subdomains from each jurisdiction obtained from internet sources-AUS (Pharmaceutical Society of Australia, 2010), CAN (Authorities, 2014), NZ (NewZealand, 2015), UK (Royal Pharmaceutical Society, 2014) and the USA (Medina et al, 2013)-were individually mapped to these (Tables 1-5). Mapping of the competencies enabling health coaching to the pharmacist competency frameworks from each The competency gaps identified from this review will contribute to the training necessary for pharmacists as health coaches in a pilot health coaching trial.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine if pharmacists from international jurisdictions meet the competencies required to health coach a comparative document analysis was used (Sandelowski, 2000). The enabling competencies for health coaches (Singh et al, 2020) were used as predefined categories for analysis, and the enabling competencies/key competencies/ competencies/ subdomains from each jurisdiction obtained from internet sources-AUS (Pharmaceutical Society of Australia, 2010), CAN (Authorities, 2014), NZ (NewZealand, 2015), UK (Royal Pharmaceutical Society, 2014) and the USA (Medina et al, 2013)-were individually mapped to these (Tables 1-5). Mapping of the competencies enabling health coaching to the pharmacist competency frameworks from each The competency gaps identified from this review will contribute to the training necessary for pharmacists as health coaches in a pilot health coaching trial.…”
Section: Designmentioning
confidence: 99%
“…The competencies enabling health coaching have been defined in a recent systematic review: (1) communicates effectively for the delivery of patient‐centered care; (2) demonstrates team and leadership skills to optimise health care; (3) demonstrates an understanding of relevant, fundamental and evidence‐based knowledge and undertakes lifelong learning to improve professional practice; (4) demonstrates tolerance and respect for individuals and groups from diverse backgrounds; (5) demonstrates professional behavior and accountability; (6) demonstrates the ability to utilise empathy when communicating with patients; (7) demonstrates confidence; (8) identifies an area for development to improve competency; and (9) works systematically and coordinates activities (Singh et al., 2020). Although the competencies enabling health coaching identify a number of different skills involved in the provision of the service (Singh et al., 2020), reports about the specifics to be included in a health coach training framework have been vague (Singh et al., 2019); other than the need to include the theoretical basis of health coaching as well as a component on motivational interviewing (Singh et al., 2019)—it is, therefore, imperative to determine if pharmacist competency frameworks in these developed countries include the competencies required to carry out health coaching.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are multiple health coaching models and theories (e.g. transtheoretical model of change, social cognitive theory, motivational interviewing), all have the common goal of inducing behavioural change [ 18 ]. Studies have shown that health coaches have been successfully used in preventive care and in managing several chronic health conditions including weight loss, physical activity and diabetes management [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The education of health coaches is also diverse and there is no comprehensive definition or license required in order to be described as a health coach [ 14 ]. Within the health care system health coaches are often health care professionals such as nurses, dieticians, psychologists or medical assistants [ 18 ]. However, some health coaches have limited or no medical education [ 14 ].This category includes health educators, professional coaches and sometimes patients or peers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 These attributes are collectively encapsulated within pharmacist health coaching services. 8,9 Pharmacist health coaching is a promising professional pharmacy service, helping participants improve the management of chronic health conditions. 8 Health coaching is a client-centered health promotion service provided to the participant by health care professionals for disease management.…”
Section: Introductionmentioning
confidence: 99%